2018
DOI: 10.1007/s00018-018-2851-7
|View full text |Cite
|
Sign up to set email alerts
|

Caveolar targeting links Kv1.3 with the insulin-dependent adipocyte physiology

Abstract: The voltage-dependent potassium channel Kv1.3 participates in peripheral insulin sensitivity. Genetic ablation of Kv1.3 triggers resistance to diet-induced weight gain, thereby pointing to this protein as a pharmacological target for obesity and associated type II diabetes. However, this role is under intense debate because Kv1.3 expression in adipose tissue raises controversy. We demonstrated that Kv1.3 is expressed in white adipose tissue from humans and rodents. Moreover, other channels, such as Kv1.1, Kv1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
3
16
0
Order By: Relevance
“…Lymphocytes concentrate Kv1.3 at the immune synapse to control Ca 2+ influx during activation [7] or at the inner mitochondrial membrane to regulate apoptosis [8]. In addition, Kv1.3 targets caveolae in adipocytes participating in the insulin-dependent signaling [9]. In myocytes, Kv11.1 is targeted to the transverse tubular network, Kv7.1 is localized to the peripheral sarcolemma and T-tubules, and, finally, Kv1.5 is concentrated at the intercalated disks and in proximity to Z-lines [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphocytes concentrate Kv1.3 at the immune synapse to control Ca 2+ influx during activation [7] or at the inner mitochondrial membrane to regulate apoptosis [8]. In addition, Kv1.3 targets caveolae in adipocytes participating in the insulin-dependent signaling [9]. In myocytes, Kv11.1 is targeted to the transverse tubular network, Kv7.1 is localized to the peripheral sarcolemma and T-tubules, and, finally, Kv1.5 is concentrated at the intercalated disks and in proximity to Z-lines [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The activity of the mitoKv1.3 channel has been reported in mitochondria from lymphocytes [23] and brain [55]. In addition, Kv1.3 was also reported in the plasma membrane of cells in the kidney [56], adipocytes [57] and epithelia [58].…”
Section: Tissue Subtype Specificity Of Potassium Channels In Mitochonmentioning
confidence: 96%
“…Although studies performed in cav-1 knockout mice revealed metabolic abnormalities [ 133 ], the underlying molecular mechanisms that link cav-1 and the caveolar network to EC metabolism are still poorly understood [ 134 ]. In adipocytes, caveolae directly participate in insulin signaling by sequestrating insulin receptor and GLUT4 and their perturbation leads to pathologic conditions related to lipid metabolism [ 135 , 136 , 137 , 138 , 139 ]. Notably, insulin resistance, defined as the lack of ability of cells to respond to insulin and to handle circulating glucose, is frequently associated with endothelial dysfunction and cardiovascular diseases.…”
Section: Origin Of Ecs and Formation Of The Vascular Threementioning
confidence: 99%